Study on Estimation of Serum Prostate Specific Antigen Level and Prostate Volume with Trans-Abdominal Ultrasonography Finding in Benign Prostate Hypertrophy at Tertiary Care Hospital : A Cross Sectional Descriptive Study - Gaire, Chandra Prakash (Birat Journal of Health Sciences, 2021)
Introduction: The periurethral and transition zones of the prostatic gland develop benign prostatic hyperplasia and represent an inevitable phenomenon for the ageing male population. Prostatic specific antigen, is a serine protease, level rises in the blood if the barrier between thelining epithelium and the blood stream is damaged. Benign prostatic hyperplasia, prostatic carcinoma and prostatitis are three common diseases where PSA in the serum is raised. Prostate volume also increases according to age, which can be estimated by trans-abdominal ultrasonography. Objective: The aim of the study is to estimate the PSA level in blood and its relationship with prostate volume in benign prostatic hyperplasia patients. Methodology: It is a descriptive cross-sectional study which was carried out between a periods of 1st April 2018 to 31st March 2019 at Birat Medical College Teaching Hospital. All the patients diagnosed with benign prostate hyperplasia at the department of urology were included in the study. Blood samples of patients were analyzed for Prostate specific antigen level estimation by chemiluminescence immunosorbent assay. Prostatic volume of the patients was measured by Transabdominal ultrasound technique. Data were entered and analyzed in Microsoft Excel. Results: A total of 68 patients were diagnosed with benign prostate hyperplasia. The mean age of the patients was 61.8±12.3 years. The maximum number 23 of patients with BPH was there in age group 51-60. The maximum no of patients 38 were having their PSA level between the range of 4.0-10.0 ng/ml. The maximum no of patients 28 was having Prostate volume in the range of 40-60 gm. The maximum number of patients 31 was having diabetes mellitus as a co-morbid association. The maximum mean PSA level and prostate volume in the patients were observed in age group >80 years,which was 20.1±8.6 ng/ml and >80 gm respectively. Conclusion: The prostate specific antigen level and prostate volume both increase in advance age group of patients suffering with benign prostate hyperplasia.